2017
DOI: 10.1186/s13046-017-0548-7
|View full text |Cite
|
Sign up to set email alerts
|

ANGPTL1 attenuates colorectal cancer metastasis by up-regulating microRNA-138

Abstract: BackgroundAngiopoietin-like protein 1 (ANGPTL1) has been reported to suppress migration and invasion in lung and breast cancer, acting as a novel tumor suppressor candidate. Nevertheless, its effects on colorectal cancer (CRC) remain poorly defined. In this study, we aim to demonstrate the biological function of ANGPTL1 in CRC cells.MethodsWe explored ANGPTL1 mRNA expression in human CRC tissues and its association with prognosis. CRC cell lines overexpressing ANGPTL1 or with ANGPTL1 knocked down were construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 28 publications
(41 reference statements)
2
47
0
Order By: Relevance
“…Co‐expression network analysis revealed that ANK2 was a hub gene associated with some validated tumor suppressors (Figure C). For example, ANGPTL1 and SPARCL1, crosstalking with ANK2, have been shown to attenuate colorectal cancer metastasis in our previous work . Hypermutated patients with higher ANK2 expression levels had a significantly better clinical outcome ( P = 0.00771, log‐rank test, Figure D).…”
Section: Resultsmentioning
confidence: 68%
“…Co‐expression network analysis revealed that ANK2 was a hub gene associated with some validated tumor suppressors (Figure C). For example, ANGPTL1 and SPARCL1, crosstalking with ANK2, have been shown to attenuate colorectal cancer metastasis in our previous work . Hypermutated patients with higher ANK2 expression levels had a significantly better clinical outcome ( P = 0.00771, log‐rank test, Figure D).…”
Section: Resultsmentioning
confidence: 68%
“…In our previous study [5], we found some of the angiopoietin-like proteins (ANGPTLs) were downregulated in CRC tissue, among which ANGPTL1 was the most signi cant one. ANGPTLs are a family of proteins that are similar to angiopoietins in structure, including ANGPTL1 to ANGPTL8 [6].…”
Section: Introductionmentioning
confidence: 94%
“…Our previous study also demonstrated that ANGPTL1 overexpression inhibited the migration and invasion of CRC cells, leading liver metastasis suppression. Besides, low expression of ANGPTL1 was related to poorer prognosis in CRC patients [5].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, significant progress is ongoing in both the prevention and treatment of lung cancer 4 . Many integrated multidisciplinary approaches to the treatment of lung cancer have improved patient outcomes, but there is an urgent need for a novel therapeutic strategy for lung cancer as there is no breakthrough treatment with long-term efficacy 5 . Specifically improved proteomics techniques for the identification, detection, and verification of biomarkers have improved our understanding of lung cancer but, early detection of lung cancer is important for a better outcome and to decrease the lung cancer mortality rate 6,7 .…”
Section: Introductionmentioning
confidence: 99%